Penerapan Prinsip Persona Non Grata Terhadap Duta Besar Ditinjau Dari Perspektif Hukum Internasional (Studi Kasus Penganiayaan TKI Oleh Duta Besar Arab Saudi Di Jerman) - Devi Yusvitasari (Universitas Pendidikan Ganesha, 2020)
A country needs to make contact with each other based on the national interests of each country related to each other, including among others economic, social, cultural, legal, political, and so on. With constant and continuous association between the nations of the world, it is one of the conditions for the existence of the international community. One form of cooperation between countries in the world is in the form of international relations by placing diplomatic representation in various countries. These representatives have diplomatic immunity and diplomatic immunity privileges that are in accordance with the jurisdiction of the recipient country and civil and criminal immunity for witnesses. The writing of the article entitled